Innovative Method and Apparatus for Deep Cleaning of Soluble Salts from Mortars and Lithic Materials. (November 2016) - Torrielli, Giulia; Gaggero, Laura; Caratto, Valentina; Ferretti, Maurizio
Abstract: A new method improves the quality and durability of decontamination by soluble salts, compared with conventional application of wraps. The salts inside the porous material are brought in solution by soaking with distilled water, then aspired by a suction nozzle applied to the sample surface, allowing the solution to move towards the surface. Finally, the method tested on plaster samples with different suction flows is effective in the cleaning. As every surface to be cleaned could be affected by different extent of deterioration, specific flows of suctions were investigated.